2022
DOI: 10.3390/biomedicines10020430
|View full text |Cite
|
Sign up to set email alerts
|

Roux-en-Y Gastric Bypass Modulates AMPK, Autophagy and Inflammatory Response in Leukocytes of Obese Patients

Abstract: Obesity is characterized by low-grade chronic inflammation, metabolic overload, and impaired endothelial and cardiovascular function. Roux-en-Y gastric bypass (RYGB) results in amelioration of the pro-oxidant status of leukocytes and the metabolic profile. Nevertheless, little is known about the precise mechanism that drives systemic and metabolic improvements following bariatric surgery. In this cohort study, we investigated the effect of RYGB on molecular pathways involving energy homeostasis in leukocytes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…This suggests that FoxG1 could be a potential target for treating brain glioma in humans (Xiao et al 2021 ). AMPK, which serves as a key controller of cellular energy balance, is frequently documented to promote autophagy by directly suppressing mTOR function or through alternative pathways (Abad-Jiménez et al 2022 ). During this investigation, it was discovered that the increase in FoxG1 expression triggers the activation of the AMPK signaling pathway, subsequently leading to the suppression of mTOR signaling.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that FoxG1 could be a potential target for treating brain glioma in humans (Xiao et al 2021 ). AMPK, which serves as a key controller of cellular energy balance, is frequently documented to promote autophagy by directly suppressing mTOR function or through alternative pathways (Abad-Jiménez et al 2022 ). During this investigation, it was discovered that the increase in FoxG1 expression triggers the activation of the AMPK signaling pathway, subsequently leading to the suppression of mTOR signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, bariatric surgery induced alterations in skeletal muscle expression of genes involved in calcium/lipid metabolism and mitochondrial function, which were associated with subsequent distinct methylation patterns at 52 weeks after surgery [ 18 ]. Furthermore, a recent study demonstrated that laparoscopic Roux-en-Y gastric bypass augmented autophagy/mitophagy markers and decreased mitochondrial membrane potential in leukocytes, improving mitochondrial turnover as a consequence [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, evidence suggests that AMPK activity is reduced in obesity, suggesting it may be a therapeutic target [ 48 ]. In this regard, we have recently reported an upregulation of this kinase after RYGB surgery [ 29 ]. This tightly coordinated process implicates several transcriptional regulators (mainly PGC1α, NRF1 and NRF2) that activate TFAM [ 49 ], thus, leading to mitochondrial transcription and mitochondrial genome replication and, in turn, to the generation of new organelles.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that this study has arisen as part of a wider project, registered in clinicaltrials.gov under the study number NCT05071391. During the course of this project, we have revealed the implication of inflammation and oxidative stress in the pathogenesis of obesity and its comorbidities and have explored in depth the mechanisms associated with RYGB-induced weight loss [ 6 , 29 ].…”
Section: Methodsmentioning
confidence: 99%